10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
ADHD coaching is both a stand-alone support and a component of multimodal care for individuals with ADHD. Still, few studies have explored whether beneficial outcomes of ADHD coaching are sustained beyond the active coaching period. A prospective mixed-methods study of a 12-session ADHD coaching engagement included a 6-week post-coaching data collection for 42 adults. In addition to the gains achieved in the pre- to immediate post-coaching period, ADHD symptoms, executive functioning, and functional impairment all showed slight improvements after a 6-week follow-up period. For executive functioning and functional impairment, the changes were statistically significant with a small effect size. While the improvements from the end of the coaching engagement to the 6-week follow-up were small, coaches, consumers, and referring practitioners should be encouraged by the durability of gains. Further longitudinal study is warranted.